Identification of Coal Seams Using Ground Penetrating Radar (GPR) Integrated with Borehole Logging Data at PIT “SWIM”, South Palembang Sub-Basin - Situmorang, Vivin Julianty; Paembonan, Andri Yadi; Andika, Putu Pradnya; Alamshah, Muhammad (Jurnal Phi: Kurnal Pendidikan Fisika & Terapan, 2026)
Coal remains one of the main energy sources in Indonesia, contributing more than 40% to national energy consumption. Therefore, an effective exploration method is needed to identify subsurface coal seams. This study aims to identify the presence of coal seams using the Ground Penetrating Radar (GPR) method integrated with borehole logging data at PIT “SWIM”, South Palembang Sub-Basin. The study utilized four GPR survey lines and four borehole log datasets. The GPR data were acquired using a 25 MHz antenna frequency and processed through the stages of move starttime, dewow filtering, automatic gain control, bandpass Butterworth filtering, background removal, running average, and topography correction Interpretation was carried out based on reflection patterns, reflector continuity, amplitude characteristics, and correlation with gamma-ray and density logs. The results indicate five coal seam zones, namely A1, A2, B, C, and D, at depths of approximately 8–60 m. Among these, Seam B exhibits the most consistent continuity across the survey lines, while Seam D appears as a prominent deeper reflector. Strong, continuous, high-amplitude reflectors indicate significant dielectric property contrasts between the coal and the surrounding lithologies. This study demonstrates that the integration of low-frequency (25 MHz) GPR and logging data can effectively support coal seam identification and illustrates the application of electromagnetic wave propagation, reflection, attenuation, and dielectric contrast principles in subsurface exploration, making it relevant to the fields of applied physics and geophysics.